Asuhan Keperawatan Komunitas pada Agregat Anak Usia Sekolah Tentang Personal Hygiene Melalui Pendidikan Kesehatan dengan Video dan Demonstrasi (IJM: Journal of Multidisiplinary, 2025)
This research aims to implement community nursing care for students at SDN Ujong Kuta Aceh Besar. The community nursing assessment was conducted on 20 students at SDN Ujong Kuta, data obtained through interviews with the principal, wishshield surveys, and distribution of questionnaires to school-age children in grade V. The results of the study showed that some students had poor habits of maintaining personal hygiene, such as dirty clothes, and lacked understanding of health information. The nursing diagnosis that emerged was the ineffectiveness of health maintenance behavior. Based on the assessment, an intervention was designed in the form of health education about personal hygiene using lecture methods, video media and demonstrations. Before and after the implementation of nursing, pre-tests and post-tests were given to participants using questionnaires that measured knowledge and behavior of participants about personal hygiene along with toothbrush demonstration practices. The evaluation results showed an increase in knowledge of 100%, and the behavior of students after being given health education was in the good category, then based on the results of observations of the toothbrush demonstration was in the good category.